Heterogeneity in the Dynamic Effects of Uncertainty on Investment - Sungje Byun; Soojin Jo (Bank of Canada, 2015)
How does aggregate profit uncertainty influence investment activity at the firm level? We propose a parsimonious adaptation of a factor-autoregressive conditional heteroscedasticity model to exploit information in a subindustry sales panel for an efficient and tractable estimation of aggregate volatility. The resulting uncertainty measure is then included in an investment forecasting model interacted with firm-specific coefficients. We find that higher profit uncertainty induces firms to lower capital expenditure on average, yet to a considerably different degree: for example, both small and large firms are expected to reduce investment much more than medium-sized firms. This highlights significant and substantial heterogeneity in the uncertainty transmission mechanism.
Keywords: E22; D80; C22; C23; 330; Econometric and statistical methods; International topics; Domestic demand and components